Sticking together or falling apart? solidarity in an era of individualization and globalization - Beer, Paul de, 1957-; Koster, Ferry (Amsterdam : Amsterdam University Press, 2009)
'This book examines, both theoretically and empirically, the impact of globalization and individualization on social solidarity. It focuses both on informal solidarity, such as volunteering, charitable giving, and informal care, and on formal solidarity, such as social benefits and development aid. It challenges the common belief that social solidarity is endangered by the increasing competition and capital flows between countries and by growing selfishness of modern citizens. The book scrutinizes the theoretical arguments that both informal solidarity and social solidarity organized through the welfare state are eroding. Empirically, it is the first thorough study of international comparative data on solidarity, globalization and individualization. The book concludes that, overall, solidarity is rising rather than declining. The impact of globalization and individualization is much more ambiguous than is often contended. While particular aspects of globalization and individualization might harm solidarity, other elements foster solidarity instead.'--Publisher's description.
Individualization, globalization and solidarity -- Taking care of each other: trends in social solidarity -- Altruism or self-interest?: solidarity and the welfare state -- Falling apart?: the many meanings of individualization -- Independent yet solidary: the impact of individualization on solidarity -- A borderless world?: developments in globalization, 1970-2005 -- Threats and opportunities: the impact of globalization on the welfare state -- Globalization versus localisation: the relationship between openness and solidarity -- Myths and facts: pressures on the welfare state -- Between community care and European welfare state: policy alternatives for the national welfare state.
Includes bibliographical references (p. 233-240) and index.
Keywords: Globalization -- Social aspects